Training is serious fun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Learning together: The agricultural worker s participatory sourcebook By S Stewart, Heifer Project International & Christian Veterinary Mission, 1998. 350 pp. ISBN 1 886532 10 9 CTA number 1045. 80 credit points